1999
DOI: 10.1002/(sici)1097-0215(19990924)83:1<113::aid-ijc20>3.3.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy of B‐cell lymphoma with cytokine gene‐modified trioma cells

Abstract: The trioma approach is a new immunotherapeutic strategy for treating B-cell lymphomas. It is based on converting the tumour idiotype to a bispecific immunoglobulin that redirects the idiotype to antigen-presenting cells. We show here that even pre-existing tumours can be eradicated by trioma vaccination, that the trioma approach is superior to vaccination with cytokine gene-modified autologous tumour cells and that there is a synergism between trioma immunisation and GM-CSF gene transfer. Furthermore, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…DCs were prepared by culturing bone marrow (BM) precursors from C57BL/6 mice in RPMI 1640 supplemented with 20% FCS, 2 mmol/L L-glutamine, 100 U/mL penicillin and streptomycin, 50 μmol/L 2-mercaptoethanol, sodium pyruvate and nonessential amino acids in the presence of 100 ng/mL granulocytemacrophage colony-stimulating factor (GM-CSF) (18) …”
Section: Cell Lines Preparation Of T Cells and Generation Of Dcsmentioning
confidence: 99%
“…DCs were prepared by culturing bone marrow (BM) precursors from C57BL/6 mice in RPMI 1640 supplemented with 20% FCS, 2 mmol/L L-glutamine, 100 U/mL penicillin and streptomycin, 50 μmol/L 2-mercaptoethanol, sodium pyruvate and nonessential amino acids in the presence of 100 ng/mL granulocytemacrophage colony-stimulating factor (GM-CSF) (18) …”
Section: Cell Lines Preparation Of T Cells and Generation Of Dcsmentioning
confidence: 99%
“…For preparation of DCs, bone marrow cells were harvested from BALB/c wild-type or CD40 Ϫ/Ϫ mice or from C57BL/6 mice and cultured in standard medium in the presence of 100 ng/mL recombinant murine granulocyte-macrophage colony-stimulating factor (GM-CSF). 29 Medium was replaced every 2 days, and a maturation step was performed at day 8 by adding 1 g/mL lipopolysaccharide (LPS) for 16 hours. If not otherwise indicated, only mature DCs were used in the experiments.…”
mentioning
confidence: 99%
“…However, for retro-and adenoviral vectors, expression levels considerably varied from cell line to cell line. It was also shown that even minute levels of GM-CSF expression are sufficient to induce effective tumor protection in in vivo model systems, 50,51 which makes GM-CSF one of the most potent immunostimulatory reagents in gene therapy. In melanoma models, GM-CSF evoked highest levels of costimulatory molecules on DCs, indicative of greatly improved functional maturation.…”
Section: Discussionmentioning
confidence: 99%
“…12 In a clinical setting, immunotherapy with GM-CSF genemodified tumor cells has also been evaluated. 49 To our knowledge, B-cell lymphomas with the exception of B-CLL cells have been transduced with GM-CSF and used as cellular vaccines to induce systemic antitumor effects, 50,53 indicating that GM-CSF is beneficial in certain malignancies in which relevant tumorassociated antigens are commonly not known. GM-CSF in our study ranks as a model cytokine demonstrating the efficient, B-cell-specific gene transfer of a potent immunostimulatory gene in conjunction with novel EBV vectors, which underscores the feasibility and proof of our concept.…”
Section: Discussionmentioning
confidence: 99%